Swimming as important factor of development of physical abilities - Popadin V.V; Goloviychuk I.N; Nomerovskij S.V (Kharkov National Pedagogical University, 2012)
The current state of health and physical fitness of young people, the complex of issues regarding the development of sports and mass swimming in Ukraine, in particular regarding training the ability to swim of the population and its conscripts have been analyzed. The role and place of swimming in the system of physical education of students and the compliance with the foundations of healthy lifestyle have been defined. The methodical peculiarities of swimming lessons with the students of higher educational institutions and their influence on physical abilities and capacities of human body are being studied. The results of studies for determination of the dynamics of physical abilities and physical fitness of students aged 18 and 19 years necessary for effective actions in terms of the average high school, taking into account means of physical training in swimming, have been presented.